Trade Risk Society—Understanding Trade Policymaking in the 2020s - Christopher M. Dent (Social Sciences)
Profound changes in trade policymaking are taking place in the 2020s in response to a complex set of increasingly salient risks shaping the international trade system. Drawing upon the influential theory of risk society, this study develops a new trade risk society framework providing original insights and new conceptual thinking on the subject. This analytical approach extends beyond merely a topical evaluation of current risks to one embedding trade in deeper underlying developments in our contemporary world and challenges facing it. Key elements of risk society theory are deployed to this end across four risk domains: 1. Economic security. 2. Geopolitical volatility. 3. Climate–environmental. 4. Technology control. Close interconnections exist between these domains, as shown in the framework’s applied analysis of the 30 or so most significant trade policymaking initiatives introduced thus far this decade up to and including US President Trump’s aggressive tariff protectionism. It is argued this pattern of initiatives are indicative of a paradigm shift in trade policy norms emerging in an increasingly volatile and contested world that can be best understood in a trade risk society context.